The Role of Organizational Learning Capability as the Mediator between Entrepreneurial Orientation and Organizational Performance in Public Organization - Rima Pusparani; Wahdiyat Moko; Sri Palupi Prabandari (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
To meet public expectations for excellent public services and good governance, the government must implement bureaucratic reform. Applying entrepreneurial principles to public organizations can boost effectiveness and efficiency in public service delivery while also fostering public values and accomplishing predetermined goals. This study investigates how the performance of public organizations is impacted by an entrepreneurial mindset. A survey of 226 managers at the Directorate General of State Assets Management, one of the Indonesian Ministry of Finance's vertical agencies, was undertaken for this study. This study used quantitative methods, and the data were analyzed using Smart-PLS. According to the findings, entrepreneurial orientation significantly and positively affects organizational performance, with organizational learning capability serving as a mediating factor in this relationship. The findings of this study have implications for how entrepreneurial orientation may boost innovation and flexibility, which in turn can help organization perform better. Organizational learning capability also helps to increase performance inside the company by enhancing the capacity to acquire and distribute information throughout the whole organization. Keywords: Entrepreneurial orientation, Organizational learning capability, Organizational performance, Public entrepreneurship